Scoping review of medical assessment units and older people with complex health needs. (23rd September 2016) - Rushton, Carole; Crilly, Julia; Adeleye, Adeniyi; Grealish, Laurie; Beylacq, Mandy; Forbes, Mark
Abstract : Objectives: To explore current knowledge of medical assessment units (MAUs) with specific reference to older people with complex needs and to stimulate new topics and questions for future policy, research and practice. Methods: A scoping review was conducted using an integrated‐latent thematic approach. Results: This review provides a unique perspective on MAUs and older people which is framed using four themes: efficiency, effectiveness, equity and time. Eighteen articles were reviewed. Most (14) articles reported on efficiency and effectiveness while none reported explicitly on equity. Time was identified as a fourth, latent theme within the literature. Conclusion: Findings from this review indicate that future policy, research and practice relating to MAUs should focus on older people with complex needs, patient‐centred metrics and those MAU characteristics most likely to deliver positive health outcomes to this particular cohort of patients.